Who Controls East Asian Corporations—and the Implications for Legal Reform - Claessens, Stijn; Djankov, Simeon; Lang, Larry H. P. (World Bank, Washington, DC, 2012)
This Note reports an analysis of ultimate control in nearly 3,000 publicly traded companies in December 1996-before the financial crisis-in nine East Asian economies: Hong Kong, Indonesia, Japan, the Republic of Korea, Malaysia, the Philippines, Singapore, Taiwan (China), and Thailand. The analysis shows that the ten largest families in Indonesia, the Philippines, and Thailand control half the corporate sector (in terms of market capitalization), while the ten largest in Hong Kong and Korea control about a third (figure 1). More extreme, in Indonesia and the Philippines ultimate control of about 17 percent of market capitalization can be traced to a single family. While the analysis shows that ownership concentration in these countries is in keeping with levels in other developing and some industrial countries, its findings shed light on the viability and vulnerability of corporate governance structures in East Asia. The concentration of corporate wealth and the tight links between corporations and government may have impeded legal and regulatory development, directly or indirectly. To create incentives for better governance, East Asian governments may have to promote more competition, even by breaking up conglomerates, and curtail related party lending by restricting ownership of banks.